Tajikistan’s agrifood sector review - Khakimov, Parviz; Ashurov, Timur; Goibov, Manuchehr; Aliev, Jovidon (International Food Policy Research Institute, 2024)
This study examines the growth and challenges in Tajikistan’s agriculture sector, highlighting its role as a key driver of the country’s development despite significant constraints and challenges, including inputs scarcity and climate change. The agriculture sector has seen an increase in gross outputs and sectoral value added, contributing to domestic needs due to population and income growth. However, Tajikistan still has the lowest agricultural value added per worker in Central Asia and remains a net importer of agrifood products, primarily due to the underdevelopment of the food processing sector. Key growth drivers include sectoral reforms, shifts in land allocation, and government incentives. Despite these efforts, regional disparities in productivity persist, and access to inputs such as fertilizers and mechanization remains limited. The paper emphasizes the need for improved access to finance, agricultural inputs, and extension services to ensure sustainable development and food security. Recommendations include enhancing the capacity of national agricultural research and development institutions, promoting climate-smart agriculture, and improving water and irrigation management. Additionally, the study underscores the importance of developing the livestock sector through improved feeding, breeding, and veterinary services. Overall, a comprehensive approach addressing policy, institutional, economic, and technological gaps is crucial for the sustainable advancement of Tajikistan’s agriculture sector.